Tool Sided Surface Modifications in the Industrial Environment - Wild, Thomas; Merklein, Marion (Lecture Notes in Production Engineering (LNPE), 2020)
In order to meet the increasing requirements on modern production, the innovative process class of sheet-bulk metal forming has proved to be suitable. Particularly lightweight construction and functional integration lead to complex shaped functional elements. In addition to this, the widespread use of high-strength materials also results in challenges in the production of such components by forming. This leads to demanding forming processes, in which the die filling is often insufficient due to unintended material flow. In this respect, tailored surfaces offer one possibility of controlling the material flow and thus increasing component quality. This concept refers to the local adaptation of the tribological system during the forming of the components. Within this research project it is the objective to transfer the process knowledge that has been generated in the Transregional Collaborative Research Centre 73 (TCRC73) to the industrial environment. This involves investigating the impact of the requirements and influences of mass production on the efficacy and service life of the tailored surface. For this purpose, based on a finely ground reference surface, the effects of abrasive blasting and laser beam polishing as surface modifications of tool steels are investigated in a laboratory and industrial scale. Emphasis is placed on the formation of the modified surfaces, the effects on the tribological operational behaviour and the impact on the fatigue behaviour of tool steels.<br